A Titanium(IV)‐Based Metal–Organic Framework Featuring Defect‐Rich Ti‐O Sheets as an Oxidative Desulfurization Catalyst. (27th May 2019) - Smolders, Simon; Willhammar, Tom; Krajnc, Andraž; Sentosun, Kadir; Wharmby, Michael T.; Lomachenko, Kirill A.; Bals, Sara; Mali, Gregor; Roeffaers, Maarten B. J.; De Vos, Dirk E.; Bueken, Bart
Abstract: While titanium‐based metal–organic frameworks (MOFs) have been widely studied for their (photo)catalytic potential, only a few Ti IV MOFs have been reported owing to the high reactivity of the employed titanium precursors. The synthesis of COK‐47 is now presented, the first Ti carboxylate MOF based on sheets of Ti IV O6 octahedra, which can be synthesized with a range of different linkers. COK‐47 can be synthesized as an inherently defective nanoparticulate material, rendering it a highly efficient catalyst for the oxidation of thiophenes. Its structure was determined by continuous rotation electron diffraction and studied in depth by X‐ray total scattering, EXAFS, and solid‐state NMR. Furthermore, its photoactivity was investigated by electron paramagnetic resonance and demonstrated by catalytic photodegradation of rhodamine 6G. Abstract : COK‐47, das erste auf Titancarboxylat‐Schichten basierende MOF, kann als reines oder defektives Nanopartikelmaterial synthetisiert werden. Seine Struktur wurde ausführlich charakterisiert; die Defekte machen es zu einem hocheffizienten Katalysator für die Oxidation von Thiophenen, außerdem zeigt es photokatalytische Aktivität.